Cathepsin B increases ENaC activity leading to hypertension early in nephrotic syndrome. Issue 10 (31st July 2019) - Larionov, Alexey; Dahlke, Eileen; Kunke, Madlen; Zanon Rodriguez, Luis; Schiessl, Ina M.; Magnin, Jean‐Luc; Kern, Ursula; Alli, Abdel A.; Mollet, Geraldine; Schilling, Oliver; Castrop, Hayo; Theilig, Franziska
Abstract: The NPHS2 gene, encoding the slit diaphragm protein podocin, accounts for genetic and sporadic forms of nephrotic syndrome (NS). Patients with NS often present symptoms of volume retention, such as oedema formation or hypertension. The primary dysregulation in sodium handling involves an inappropriate activation of the epithelial sodium channel, ENaC. Plasma proteases in a proteinuria‐dependent fashion have been made responsible; however, referring to the timeline of symptoms occurring and underlying mechanisms, contradictory results have been published. Characterizing the mouse model of podocyte inactivation of NPHS2 (Nphs2 ∆pod ) with respect to volume handling and proteinuria revealed that sodium retention, hypertension and gross proteinuria appeared sequentially in a chronological order. Detailed analysis of Nphs2 ∆pod during early sodium retention, revealed increased expression of full‐length ENaC subunits and αENaC cleavage product with concomitant increase in ENaC activity as tested by amiloride application, and augmented collecting duct Na + /K + ‐ATPase expression. Urinary proteolytic activity was increased and several proteases were identified by mass spectrometry including cathepsin B, which was found to process αENaC. Renal expression levels of precursor and active cathepsin B were increased and could be localized to glomeruli and intercalated cells. Inhibition of cathepsin B prevented hypertension. With the appearance of gross proteinuria, plasmin occurs in the urine and additional cleavage of γENaC is encountered. In conclusion, characterizing the volume handling of Nphs2 ∆pod revealed early sodium retention occurring independent to aberrantly filtered plasma proteases. As an underlying mechanism cathepsin B induced αENaC processing leading to augmented channel activity and hypertension was identified.